Temporal dynamics and vertical variations in stem CO2 efflux of Styphnolobium japonicum - Han, Fengsen; Wang, Xiaolin; Zhou, Hongxuan; Li, Yuanzheng; Hu, Dan (Journal of plant research, 2017)
CO 2 efflux (E CO2 ) from stems and branches is highly variable within trees. To investigate the mechanisms underlying the temporal dynamics and vertical variations in E CO2 , we measured the stem E CO2 by infrared gas analysis (IRGA) and meteorological conditions at 10 different heights from 0.1 to 3.7 m aboveground on two consecutive days every month for 1 year in six Styphnolobium japonicum trees with a similar size. The results indicated that the seasonal change in E CO2 roughly followed the seasonal variations in woody tissue temperature (T W ) and stem radial diameter increment (Di). Together, T W and Di explained the monthly change in E CO2 , and the contributions of T W and Di changed with the stem positions and growth stages. The diurnal patterns of E CO2 differed greatly between the growing and dormant season, showing a bimodal distribution with an obvious midday depression in the former and a unimodal distribution in the latter. The strong vertical variation in the day-time E CO2 of the growing season was mainly caused by the vertical gradients of T W , Di and difference in sapwood volume per unit of the stem surface along the trunk. The temperature-sensitivity coefficient (Q 10 ) was not constant, as assumed in some models, but was instead vertically altered and highly dependent on the measurement temperature. For all stem positions, the highest Q 10 value appeared at approximately 5 °C, and both higher and lower temperatures decreased Q 10 . Our study demonstrated that application of a constant Q 10 would cause an estimation error when scaling up chamber-based measurements to annual carbon budgets at the whole-stem level.